Podmiotowość spółek osobowych w prawie szwajcarskim: [Legal personality status of partnerships in swiss law] (Studia Prawnicze / The Legal Studies, 2008)
Problem podmiotowości prawnej spółek osobowych, a zwłaszcza spółki cywilnej, stanowi wciąż wyzwanie dla doktryny i orzecznictwa. Od dziesięcioleci trwają spory, co do natury prawnej spółki cywilnej i osobowych spółek handlowych. Napisano na ten temat wiele artykułów i innych opracowań . W ostatnich latach spór, co do istoty spółki cywilnej rozgorzał z nową siłą. Ukazały się też obszerne opracowania poświęcone spółce cywilnej, w tym problemowi jej podmiotowości prawne. Warto więc skonfrontować poglądy reprezentowane w polskiej doktrynie ze stanowiskiem doktryny i orzecznictwa tych państw, w których przyjęto podobne rozwiązania normatywne, zwłaszcza jeżeli były one pierwowzorem dla ustawodawstwa polskiego. Żródłem sporów o podmiotowość spółek osobowych jest instytucja wspólności do niepodzielnej ręki, która dotarła do naszego systemu prawnego z Niemiec. Słusznie więc doktryna prawa spółek nawiązuje najczęściej do prawa niemieckiego.  The problem of legal status of partnerships belongs to the most hotly dis puted issues in European corporate law In Polish literature, no analyses have been published explaining the viewpoint of the Swiss doctrine. In spite of many simi larities between legal solutions applied in Swiss and Polish law systems, a signifi cant difference exists in approach to the mentioned problem. In Poland, the most common standpoint relies on treating civil partnerships as obligation, while the Swiss doctrine has abandoned this position and treats civil partnership (Einfache Gesellschaft) as a legal group of joint interests, ie a type of organizational unit. In relation to commercial partnerships, a very similar norm has been adopted in Polish Commercial Companies Code (art. 8 § 1), and in Swiss Code of Obliga tions in art. 562. In Poland, the above norm is generally understood as leading to legal capacity of commercial partnerships, while in Switzerland legal capacity of such partnerships is normally rejected. In effect of the existence of legal loop holes, as well as the influence of strong legal tradition, Swiss doctrine faces the problem of the legal capacity of civil partnerships, including in particular busi ness partnerships, as well as the problem of legal capacity of commercial partner ships. In both cases, Swiss doctrine has been following two divergent tendencies: the former leading to rejection of legal capacity in effect of the adoption of joint and indivisible ownership of assets (Gesamthand) in such partnership, and the latter, accepting the mentioned partnerships as legal entities, in effect of the ne cessities of trade, in particular those related to the managing the business organi zation under own trade name or brand. Until now, Swiss law has not followed in the footsteps of German legal system, and refused to accept the legal capacity of either civil partnership or commercial partnerships.